Environmental considerations in Nigerian agricultural policies, strategies and programs - Olawumi, Ayodele (International Food Policy Research Institute, 2009)
Agriculture is the major sector upon which the majority of Nigeria’s rural poor depend on for their livelihood. Over 70 percent of the active labor force is employed in agriculture (World Bank 2007). The federal government of Nigeria (FGN) has identified agriculture as the key development priority in its efforts to halve poverty by 2015 and diversify the economy away from the oil sector. The FGN is designing strategies to increase agricultural production, processing, and marketing. Some of these are tied to the National Economic Empowerment and Development Strategy (NEEDS), which the government designed in 2004 to reduce poverty and empower the poor. Given the importance of agriculture in poverty reduction, NEEDS sets out a number of qualitative performance targets that were to be achieved by 2007. These include 6 percent annual growth in agricultural export and a drastic reduction in food import from 14.5 percent of total imports to 5 percent. The “Seven Point Agenda” of the present administration specifies “food security “as one of the priorities in the country’s “Medium Term Development Plan and Vision 20: 2020.”